Alternative splicing signature of alveolar type II epithelial cells of Tibetan pigs under hypoxia-induced - Yuan, Haonan; Liu, Xuanbo; Wang, Zhengwen; Ren, Yue; Li, Yongqing; Gao, Caixia; Jiao, Ting; Cai, Yuan; Yang, Yanan; Zhao, Shengguo (Frontiers in Veterinary Science, 2022)
Alternative splicing (AS) allows the generation of multiple transcript variants from a single gene and affects biological processes by generating protein diversity in organisms. In total, 41,642 AS events corresponding to 9,924 genes were identified, and SE is the most abundant alternatively spliced types. The analysis of functional categories demonstrates that alternatively spliced differentially expressed genes (DEGs) were enriched in MAPK signaling pathway, HIF-1 signaling pathway, and proteoglycans in cancer between normoxic (21% O2, TN, LN) and hypoxic (2% O2, TL, LL) groups, including SLC2A1, HK1, HK2, ENO3, and PFKFB3 may rapid proliferate alveolar type II epithelial (ATII) cells through increase in the intracellular levels of glucose and quickly diverted to anabolic pathways by glycolysis intermediates under hypoxia. ACADL, EHHADH, and CPT1A undergo one or two AS types with different frequencies in ATII cells between TN and TL groups (excluding alternatively spliced DEGs shared between normoxic and hypoxic groups), and may be a constant supply of lipids were obtained either from the circulation or de novo synthesis for better growth of ATII cells under hypoxia condition. MCM7 and MCM3 undergo different AS types between LN and LL groups (excluding alternatively spliced DEGs shared between normoxia and hypoxia groups), may bind to the amino-terminal PER-SIM-ARNT domain and the carboxyl terminus of HIF-1α to maintain their stability. Overall, AS and expression levels of candidates mRNAs between Tibetan pigs and Landrace pigs revealed by RNA-seq suggest their potential involvement in the ATII cells growth under hypoxia condition.